A multi-color video-ophthalmoscopes allows to measure the spectral distribution of light absorption of blood in the human retina - Tornow, Ralf-Peter; Odstrcilik, Jan; Kolar, Radim (Frontiers in Medicine, 2023)
Based on our previously developed mono-color video-ophthalmoscope a multi-color video-ophthalmoscope was developed. Using narrow band transmission filters, this instrument allows to measure the pulsatile cardiac cycle induced blood volume changes in the human retina for any wavelength in the sensitivity range of the used CMOS-camera. In this key experiment, video sequences (8 s, 25 fps, 200 frames) of the optic nerve head (ONH) were acquire for seven wavelengths between 475 nm and 677 nm one after the other. After image registration of all frames of each video sequence (to compensate for eye movements) and trend correction (to compensate for slow intensity changes), the amplitude of the cardiac cycle induced light intensity changes (pulsatile absorption amplitude PAA) can be calculated for all seven wavelengths. The results confirmed that the spectral distribution of PAA (λ) follows the distribution of the light absorption of blood. The measured values correspond to the absorption of a thin blood layer of about 0.5 μm thickness.